Police Speak and Narrative Storytelling in Knives Out Movie Script: A Forensic Linguistic Perspective - Ratminto Dwi Ananta (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2021)
This research investigates a tragic murder case from Knives Out movie of Harlan Thrombey case Fran was a servant in the Thrombey Family, and the investigator immediately investigated the case and emphasized the outline of the law, language, and criminal cases in the field of forensic linguistics. This research aimed to describe Police speak and Narrative Storytelling in Knives Out Movie Script (A Forensic Linguistic Perspective). The method used descriptive qualitative, the data was taken from the movie script and then collects every discovery through any existing data and analyzed by interpreting and describing the data. This result was to focus on how the police speak and narrative storytelling depicted in the movie â€œKnives Out 2019â€ by â€œRian Johnsonâ€ was focused in terms of its forensic linguistics. In many investigative languages â€‹â€‹that have not been revealed by the investigator in their interviews with each of the witnesses. This research describes the context of the data using Narrative and Storytelling and also how police detectives interview witnesses using Policespeak, including control over topic and interactional focus, establish motive, establish knowledge, rapport building, and control of topic navigation by interpreting and describing data using police speak and narrative storytelling theory to reveal the language of the police investigation. From the findings that Harlan Thrombey found died cause he was suicide, Harlan took the knife to kill himself however Harlan knew about which one will kill him by criminal, someone changed his morphine into overdoses and that was Ransom, his nephew.